COMMUNICATIVE LANGUAGE TEACHING IN ACADEMIC LYCEUMS - UMAROVA VAZIRA KHOLMURAD QIZI, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation:  This  article  examines  the  implementation  of  Communicative Language Teaching (CLT) in academic lyceums. CLT focuses on developing students’ communicative  competence  by  encouraging  real-life  interaction  and  meaningful language use. The paper discusses the principles of CLT, its advantages, and practical techniques  for  classroom  application.  Special  attention  is  given  to  the  role  of  the teacher, student engagement, and the challenges faced in academic lyceums. The article highlights how CLT can improve students’ speaking, listening, and overall language proficiency.